STUDENTS’ RESPONSE TOWARD THE COMPETENCIES OF TEACHERS: AN EXPLORATORY STUDY - Novitasari, Susi; Noviani, Sulis; Murtini, Iin (JURNAL PENA SAINS, 2024)
Teachers are one of the main key holders of the success of an education process. As the spearhead of education, the ability of teachers determines the success of education. Teachers apply their competences in conducting the learning process. This research aims to determine students’ responses toward the integrity of honorary teachers and civil servant teachers in the Lamongan, Tuban and Bojonegoro residency areas. The method used in this research is a qualitative approach using a questionnaire distributed via Google Form to high school or equivalent students in several residency areas in Lamongan, Tuban and Bojonegoro. As well as literature studies to strengthen the information we obtain through library materials in the form of previous research articles that are relevant to the topic discussed. There are several differences in the responses of high school or equivalent students in the Lamongan, Tuban and Bojonegoro residency areas regarding the integrity of honorary teachers and civil servant teachers. Regarding the timeliness of starting and ending lessons, the percentage of discipline for honorary teachers is higher than that of civil servant teachers, in creating and using learning media, honorary teachers are more creative; in giving pre-tests and post-tests, honorary teachers carry them out more often. However, in terms of behavioral discipline when teaching in class, civil servant teachers are more disciplined than honorary teachers and in explaining material in class, students more easily understand the material presented by civil servant teachers. To conclude, teachers must have high integrity as educators, namely acting consistently between what has been said or taught with behavior in accordance with the values of a teacher, namely honesty, responsibility and discipline.